The Association Between Burnout and Pediatrician Management of Adolescent Depression. (July 2020) - LaLonde, Leah; Bruni, Teryn; Lancaster, Blake; Maragakis, Alexandros
Objective: Given the increased demand for pediatric primary care providers to manage adolescent depression, the current study examines the association between burnout and provider comfort and perception of feasibility managing adolescent depression.Method: Data were collected from 52 pediatricians at a Midwest academic health center.Results: Higher scores on depersonalization were associated with lower provider-reported comfort managing adolescent depression. Emotional exhaustion and personal accomplishment were not associated with provider-reported comfort managing adolescent depression. None of the burnout domains were associated with the provider-reported perception of the feasibility managing adolescent depression in this setting. Limitations and recommendations for future research regarding the impact of behavioral health training on burnout are discussed.Conclusions: The interpersonal stress dimension of burnout is associated with less comfort managing depression. Adding positive systematic interventions, such as behavioral health trainings that support pediatricians in the management of behavioral health may have impact on burnout.